An excuse to think in the General Theory of Labour Law: The necessity to demand payment of profits - Neves Mujica, Javier (2016)
This article addresses the antinomy concerning to profit sharing to the workers. Through an analysis of the classic criteria of antinomy solutions and particulars of the Labour Law, the author recognize the prevalence of the classic criteria.